Effects of artificial light at night (ALAN) on the development and behaviors of zebrafish in early life stages - Liting Zhao; Jie Tang; Kun Chen; Yanhong Shi; Weiwei Feng; Xiaohong Xu; Xuchun Qiu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Dihydromyricetin-loaded TPGS/gelatin grafted-β-Cyclodextrin/ chitosan grafted-β-Cyclodextrin nano-delivery system for improving oral absorption - Ling Tang; Jinqing Chen; Jiali Luo; Huijuan Wei; Lina Lan; Hailan Qin; Qiumei He; Xiangyu Kong; Liting Lai; Wenya Ding; Jian Xiao (Food Research International, 2026)

Assessment of ultrasonic vocalization-mediated communication deficits in AD rats: A social learning paradigm using conspecific drinking behavior - Xinxiang Su; Junjun Pu; Jinxia Liao; Yuqian Tang; Liting Feng; Zhen Wu (Behavioural Processes, 2026)

Chiral multilevel-structured hydroxyapatite nano-bacterial cellulose membrane with anti-inflammatory activity and regulation of immune microenvironment promotes wound healing in the elderly - Jiawen Zhao; Yuan Zong; Tong Wu; Yi Yang; Lei Li; Wenshuo Tang; Xiaoyu Zhao; Xianfei Xie; Yiming Gao; Chao Zhou; Ning Li; Liting Jiang (Chemical Engineering Journal, 2025)

Genome-wide analysis and functional validation of the GH1 gene family in cotton under salt stress - Liting Zhang; Junfeng Tang; Xiaoyu Tian; Hui Fang; Yifan Xu; Yiming Qian; Mengxue Jia; Ping Li; Baohua Wang; Zhimin Zhuang (Functional & Integrative Genomics, 2025)

A versatile fluorescent probe for the ratiometric detection of hydrazine (N2H4) in water, soil, plant, and food samples - Yan Pan; Liting Tang; Lin Li; Xiongzhi Wu; Liqiang Yan (Environmental Pollution, 2024)

Recent Advances in Organic Small-Molecule Fluorescent Probes for the Detection of Zinc Ions (Zn2+) - Junjie Yang; Liting Tang; Lin Li; Xiongzhi Wu; Liqiang Yan (Journal of Fluorescence, 2024)

Combined effects of copper and cadmium exposure on ovarian function and structure in Nile Tilapia (Oreochromis niloticus) - Yijie Wu; Ting Huang; Qiyu Wei; Xin Yan; Liting Chen; Zhirui Ma; Liming Luo; Jinling Cao; Hongxing Chen; Xinxian Wei; Honglian Tan; Fuyan Chen; et al. (Ecotoxicology, 2024)

Atlas and source of the microplastics of male reproductive system in human and mice - Wen Yang; Longmei Wu; Guanjian Li; Lan Shi; Junqiang Zhang; Liting Liu; Yuge Chen; Hui Yu; Kai Wang; Lei Xin; Dongdong Tang; Qunshan Shen; et al. (Environmental Science and Pollution Research, 2024)

The Effect of Copper–Cadmium Co-Exposure and Hormone Remediation on the Ovarian Transcriptome of Nile Tilapia (Oreochromis niloticus) - Yijie Wu; Liting Chen; Xin Yan; Jun Xiao; Zhirui Ma; Zhanyang Tang; Zhongbao Guo; Liping Li; Guixiang Tong; Honglian Tan; Fuyan Chen; Xinxian Wei; et al. (Fishes, 2024)
The escalating problem of copper (Cu) and cadmium (Cd) pollution in aquatic environments poses a significant threat to the ovarian tissue and reproductive capacity of fish, hindering the development of the aquaculture industry. However, the combined effects of Cu and Cd on fish gonadal development remain unclear. In this study, the fish species Nile tilapia was stressed with rearing water containing 300 μg/L Cu2+ and 100 μg/L Cd2+ for 30 days, followed by an intraperitoneal injection of luteinizing hormone-releasing hormone (LHRH-α) and human chorionic gonadotropin (HCG) at various concentrations. We investigated the ovarian transcriptome profiles before and after injection. Prior to injection, combined treatment with Cu and Cd resulted in reproductive dysfunction and metal ion imbalance in tilapia. Transcriptomic profiling revealed differential gene annotation concentrated in the MAPK signaling pathway and regulation of GTPase activity. Post-injection, all concentrations of LHRH-α and HCG groups showed an upregulated gonadosomatic index (G.S.I) and higher levels of vitellogenin (VTG), gonadotropin-releasing hormone (GnRH), gonadotropin (GTH), and estrogen (E2) in serum compared to the negative control group. Transcriptomic analysis revealed alterations in various ovarian signaling pathways, preliminarily revealing the in vivo molecular mechanisms and differences in LHRH-α and HCG. The findings from this study could help us better understand how to counteract the effects of combined Cu and Cd exposure on tilapia ovarian development, which has significant implications for the Nile tilapia aquaculture industry.

Genome-wide analysis of BrbHLH gene family and functional identification of the involvement of BcbHLH57 in abiotic stress in wucai (Brassica campestris L.) - Bingsheng Zhang; Liting Zhang; Tian Lan; Shidong Zhu; Jinfeng Hou; Guohu Chen; Xiaoyan Tang; Defang Gan; Chenggang Wang; Lingyun Yuan (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)
Wucai ( Brassica campestris L. ssp. chinensis var. rosularis Tsen) is a subspecies of Brassica campe stris , is a kind of cold-tolerant vegetable widely cultivated in the Yangtze-Huai River Basin of China. To breed new varieties of resistance to stress, it is necessary to study the tolerance of Resistance to different stresses. Transcriptomic data showed that exogenous application of 2, 4-epbrassinolide (EBR) significantly increased the bHLH genes expression in wucai at low temperature, and bHLH57 was up regulated significantly. BHLH (Basic helix-loop-helix) TFs (transcription factor) is a superfamily of TFs with complex functions and related to various plant life activities. In this study, a total of 239 bHLH genes were identified, and their amino acid physicochemical properties, chromosome location, gene structure, phylogeny and cis-acting elements were analyzed by bioinformatics. Phylogenetic analysis showed that bHLH gene families in Brassica rapa and Arabidopsis were divided into six groups, and the distribution of bHLH genes in Brassica rapa was uneven. The BrbHLH s were irregularly mapped in the cultivated B. rapa genome. The maximum number (40) of BrbHLH genes were mapped on Chr09. In addition, there were tandem repeats in some genes. The collinearity analysis showed that 152 AtbHLH genes and 239 BrbHLH protein genes formed 296 collinearity pairs, and the Ka/Ks ratio ofall duplicated BrbHLH gene pairs had a Ka/Ks ratio of < < 1, indicating that the bHLH family genes may have undergone strong purification and selection during the evolution process. Cis-acting elements analysis showed that the promoter region of bHLH family genes in Brassica rapa had more responsive elements related to light, hormone and abiotic stress. The BcbHLH57 overexpressing Arabidopsis thaliana lines were subjected to different stress treatments, and the seed germination rate, root growth, survival rate and various plant physiological indexes were determined. The results showed that the transgenic lines were more tolerant to salt, heat and drought stress. In this study, the response of BcbHLH57 gene to salt, heat and drought stress was reported for the first time, which provided a basis for further research on the function of BcbHLH57 in abiotic stress.

Recent progress of photoelectrocatalysis systems for wastewater treatment - Qi Dang; Liting Wang; Jiqing Liu; Dejin Wang; Jianfei Chai; Minghong Wu; Liang Tang (Journal of Water Process Engineering, 2023)

Effects of four hormones on the mitigation of ovarian damage in tilapia (Oreochromis niloticus) after copper and cadmium exposure - Yijie Wu; Ting Huang; Xin Yan; Jun Xiao; Zhirui Ma; Liming Luo; Liting Chen; Jinling Cao; Zhanyang Tang; Xinxian Wei; Fuyan Chen; Yu Zhu; et al. (Aquatic Toxicology, 2023)

Manipulating Ga growth profile enables all-flexible high-performance single-junction CIGS and 4 T perovskite/CIGS tandem solar cells - Jun Luo; Liting Tang; Shijin Wang; Hui Yan; Wuji Wang; Zheng Chi; Junbo Gong; Jianmin Li; Xudong Xiao (Chemical Engineering Journal, 2023)

Distribution and Characteristics of Microplastics in Barnacles and Wild Bivalves on the Coast of the Yellow Sea, China - Tao Zhang; Kexin Song; Liting Meng; Ruikai Tang; Tongtong Song; Wei Huang; Zhihua Feng (Frontiers in Marine Science, 2022)
Barnacles and bivalves are two well-known sessile invertebrates that play important roles in marine ecosystems. Microplastic (MP) pollution has attracted widespread attention. Barnacles and wild bivalves are smaller than farmed individuals; thus, they may be more sensitive to MPs. However, less is known about the abundance and spatial distribution of MPs in wild bivalves along with the coastal areas of China. This study evaluates MP pollution in the most abundant bivalves and barnacles ( Crassostrea gigas , Ostrea cucullata , Mytilus edulis , and Balanus albicostatus ) at five stations in the intertidal zone of the Yellow Sea. B. albicostatus was divided into ecotype A and ecotype B. The abundance of MPs in barnacles, wild bivalves barnacles, and wild bivalves varied from 0 to 2.25 items/individual and 0 to 118.21 items/g. O. cucullata and B. albicostatus (ecotype A) had the highest abundance of MPs, with average abundances of 0.56 ± 0.36 items/individual and 21.59 ± 27.26 items/g, respectively. The types of MPs found in bivalves and barnacles include fibers, fragments, films, and microbeads. The most abundant size was less than 1,000 μm, which accounted for 53% of the total MPs. Cellophane (CP), polypropylene (PP), polyethylene (PE), and polyethylene terephthalate (PET) were the main polymer types in bivalves and barnacles. This study suggests that the abundance of MPs in wild bivalves is close to that of farmed bivalves with commercial specifications, despite their smaller size. The MP abundance of barnacles in the Yellow Sea is higher than that in other areas in terms of items per gram. In addition, the ecological type may affect the ability of barnacles to accumulate MPs. Ingestion of MPs by barnacles and wild bivalves should be of concern because they may enter the human body through the food web and may pose a potential threat to human health.

HGF can reduce accumulation of inflammation and regulate glucose homeostasis in T2D mice - Liting Yan; Xiaoxi He; Yinghua Tang; Xiaomin Zhao; Gang Luo; Xinhong Wang (Journal of Physiology and Biochemistry, 2021)

AFAP1-AS1: a rising star among oncogenic long non-coding RNAs - Fang Xiong; Kunjie Zhu; Su Deng; Hongbin Huang; Liting Yang; Zhaojian Gong; Lei Shi; Yi He; Yanyan Tang; Qianjin Liao; Jianjun Yu; Xiaoling Li; et al. (Science China Life Sciences, 2021)

Functional Differences Between Two Kv1.1 RNA Editing Isoforms: a Comparative Study on Neuronal Overexpression in Mouse Prefrontal Cortex - Liting Zhang; Zetong Peng; Wenjun Bian; Pingping Zhu; Bin Tang; Wei-Ping Liao; Tao Su (Molecular Neurobiology, 2021)